Viabilty Test of Fish Scales Collagen Gourami (Oshpronemus Gouramy) on Human Gingival Fibroblasts Cells - Widya Rizky Romadhona Widya (Journal of Stem Cell Research and Tissue Engineering, 2022)
Periodontal disease is a pathological inflammatory condition of the periodontal tissues surrounding the teeth, including Human Gingival Fibroblasts (HGF) which is one of the major components of tissue formation in periodonsium. HGF regeneration with the accelerating proliferation of tissue engineering therapy needs. Generally, the tissue engineering using regenerative materials from cow or pig as the therapies, but these materials have some flaws so this research to find alternative materials regenerative tissue engineering scaffold collagen type 1 derived from fresh water fish scales, one of which are gourami fish scales. This research was conducted to test the viability of fish scales collagen gouramy against Human Gingival Fibroblasts for 24 hours. This study aimed to determine the concentration of fish scale collagen gourami which can maintain the viability of human gingival fibroblast cells for 24 hours. HGF is taken from healthy gingiva and planted in 96 well plates. Fish scales collagen gouramy with a concentration of 0.32 mg/ml, 0.16 mg/ml, 0.04 mg/ml, 0.02 mg/ml and 0.01 mg/ml were added to each well and incubated during 24 hours. MTT Assay is performed to see the viability of fibroblast cells. The viability of HGF were increased after the addition of fish scales collagen gourami on concentration 0.32 mg/ml until 0.01 mg/ml. The highest viability of the cells was shown after the addition of 0.01 mg/ml. Fish scales collagen gouramy has the potential in tissue engeneering and the concentration of 0.01 mg/ml shows the highest viability of HGF.